2013
DOI: 10.1089/jpm.2012.0555
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Dutch General Population in Advance Care Planning: A Cross-Sectional Survey

Abstract: Although the majority of the Dutch population seems open to discussions about end-of-life care, our study revealed that discussions with physicians are exceedingly rare. To improve ACP as a joint process among patients, relatives, and physicians, the general public's awareness of the importance of end-of-life discussions with their physicians needs to be increased and physicians need to play a more active role by initiating conversations and dialogue regarding end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 44 publications
(62 reference statements)
4
45
2
Order By: Relevance
“…For appointing ACD, age was strongest predictor which reflects the tendency found internationally for more planning for, and experience of, death and illness at a later age. [25][26][27] For instructional ACD, being female was associated with higher completion of this document, again consistent with some international studies, 28,29 although others found no gender-based differences. 20,30,31 Most significant, however, is the finding that instructional ACD were associated with a person who has had their own 'health scare'.…”
Section: Discussionsupporting
confidence: 89%
“…For appointing ACD, age was strongest predictor which reflects the tendency found internationally for more planning for, and experience of, death and illness at a later age. [25][26][27] For instructional ACD, being female was associated with higher completion of this document, again consistent with some international studies, 28,29 although others found no gender-based differences. 20,30,31 Most significant, however, is the finding that instructional ACD were associated with a person who has had their own 'health scare'.…”
Section: Discussionsupporting
confidence: 89%
“…Only the difference in awareness of the term ACP was not significant after adjustment. This finding that older age, higher education and worse health status are associated with ACP engagement is consistent with data from other cross-sectional studies from Alberta21 and elsewhere 11 12. The trend of increased engagement in discussing and documenting end-of-life care preferences has also been seen in USA between 2002 and 2010 14…”
Section: Discussionsupporting
confidence: 88%
“…Despite an increasing international consensus on the benefits of ACP,6 low levels of public engagement remain a concern 9. A meta-analysis in the palliative care context10 and cross-sectional studies of the public11 12 have explored the reasons for this, but there is a paucity of longitudinal data about whether public engagement in ACP activities is changing over time 13 14. To address this gap in time series data, we have examined for trends in public engagement in elements of ACP using raw data from three independently administered public surveys, conducted in a single Canadian province in 2007, 2012 and 2013.…”
Section: Introductionmentioning
confidence: 99%
“…) and 7% in the Netherlands have completed ADs (Raijmakers et al . ). Furthermore, in Australia, only 1%–7.9% of individuals, including patients in residential care facilities (Nair et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, AD utilisation was found to be relatively low. Only 25%-30% of the general public in the USA (Rao et al 2014) and 7% in the Netherlands have completed ADs (Raijmakers et al 2013). Furthermore, in Australia, only 1%-7.9% of individuals, including patients in residential care facilities (Nair et al 2000, Taylor et al 2003, have completed ADs.…”
Section: Introductionmentioning
confidence: 99%